HUBUNGAN FAKTOR PREDISPOSISI DENGAN PERILAKU PENCEGAHAN KEPUTIHAN PATOLOGIS PADA MAHASISWA KEBIDANAN JAKARTA - Fauziah Yulfitria Yulfitria; Aticeh Aticeh Aticeh; Nina Primasari Primasari (Jurnal Ilmu dan Teknologi Kesehatan, 2015)
Vaginal discharge is a problem that is often experienced by women in various ages. According to the World Health Organization (WHO) about 75% of women in the world will experience vaginal discharge and in Indonesia around 90% of women experience vaginal discharge potential. Discharge can be experienced by unmarried women or adolescent girls aged 15-24 years. From some of the results, the data is still a lot of teenagers have good behavior on the prevention and treatment of vaginal discharge. Of unacceptable behavior towards the prevention and treatment of vaginal discharge can cause pathological vaginal discharge. The aim to determine the relationship predisposing factors (Knowledge, Attitude and Perception) with pathological discharge prevention behaviors in Jakarta midwifery students. Descriptive Analytical Methods with cross sectional data collection. The number of samples in this study of 98 respondents, the sampling using stratified random sampling. The data used are primary data by giving questionnaires to respondents. RESULTS: There is a relationship between attitudes (p-value = 0.001) with a pathological vaginal discharge prevention behaviors in Jakarta midwifery students. Conclusion: Prevention of pathological vaginal discharge related with attitude but not related to the knowledge and perception.